Digital System Integration in Educational Management: A Path to Adaptive and Successful Education in Islamic Institutions - Chilya Aghnis Shalicha; Muhammad Alghiffary (State Islamic Institute of Madura, 2025)
Digital transformation has reshaped the global educational landscape, yet Islamic educational institutions in Indonesia—particularly madrasahs and pesantren—continue to encounter substantial barriers in adopting technology. This study investigates the application of digital systems in educational management through an adaptive learning framework as a means of enhancing effectiveness and accountability in the digital era. Employing a library research method, the analysis draws upon a wide range of scholarly literature concerning the digitalization of educational management, adaptive learning, and the integration of technologies such as artificial intelligence (AI), learning analytics, and the VARK (Visual, Auditory, Read/Write, Kinesthetic) model. Findings indicate that digital systems can improve operational efficiency by up to 40%, enable personalized learning experiences, and facilitate data-driven decision-making. AI-based adaptive learning demonstrates a potential increase in learning outcomes of up to 25%, particularly in inclusive education for students with special needs. Nevertheless, implementation remains constrained by inadequate technological infrastructure, limited digital literacy among educators, cultural resistance within institutions, and financial limitations. To address these challenges, this study proposes a comprehensive strategy encompassing equitable investment in infrastructure, sustainable capacity development for educators, multi-stakeholder collaboration, the creation of digital content rooted in Islamic values, and continuous evaluation informed by feedback. Within the context of Islamic education, technological integration must reinforce spiritual, moral, and ethical dimensions alongside technical efficiency. This research contributes to the development of a holistic conceptual framework for digital education management and offers practical recommendations for policymakers in advancing inclusive, effective, and sustainable education in the digital era.